High‐Performance Organic Solar Modules via Bilayer‐Merged‐Annealing Assisted Blade Coating. Issue 28 (6th June 2022) - Fan, Jing‐Yuan; Liu, Zhi‐Xi; Rao, Jack; Yan, Kangrong; Chen, Zeng; Ran, Yixin; Yan, Buyi; Yao, Jizhong; Lu, Guanghao; Zhu, Haiming; Li, Chang‐Zhi; Chen, Hongzheng
Abstract: Although encouraging progress is being made on spin‐coated prototype cells, organic solar cells (OSCs) still face significant challenges, yet to be explored, for upscaling the multi‐stacked photoactive layers in the construction of large‐area modules. Herein, high‐performance opaque and semitransparent organic solar modules are developed via a bilayer‐merged‐annealing (BMA)‐assisted blade‐coating strategy, achieving impressive efficiencies of 14.79% and 12.01% with respect to active area of 18.73 cm 2, which represent the best organic solar minimodules so far. It is revealed that the BMA strategy effectively resolves the de‐wetting issues between polar charge transport layer solution and non‐polar bulk heterojunction blends, hence improving the film coverage, along with electronic and electric contacts of multi‐stacked photoactive layers. As result, organic solar modules coated under ambient conditions successfully retain the high‐efficiency of small‐area cells upon 312 times area scaling‐up. Overall, this work provides a facile and effective method to fabricate high‐performance organic solar modules under ambient conditions. Abstract : High‐performance organic solar modules by blade coating are developed via a bilayer‐merged‐annealing strategy, achieving impressive power conversion efficiency of 14.79% with an active area of 18.73 cm 2, which represents the best organic solar minimodule by blade coating so far.